2023
DOI: 10.1038/s41398-023-02553-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of cardiovascular risk factors and lifestyle behaviors with neurodegenerative disease: a Mendelian randomization study

Abstract: Previous observational studies reported that midlife clustering of cardiovascular risk factors and lifestyle behaviors were associated with neurodegenerative disease; however, these findings might be biased by confounding and reverse causality. This study aimed to investigate the causal associations of cardiovascular risk factors and lifestyle behaviors with neurodegenerative disease, using the two-sample Mendelian randomization design. Genetic variants for the modifiable risk factors and neurodegenerative dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated implications of downregulated circFASTKD1 and circGF2I (Gao WQ et al 2020 ; Yuan C et al 2022 ) associated with myocardial infarction. Similarly, these circRNAs have also been observed in an intersection between cardiovascular and neurodegenerative disease pathways (Huang L-Y et al 2023 ). Furthermore, the linear counterpart of the PICALM’s dysregulation influences the risk of AD development by impacting APP processing, Aβ transcytosis and tau progression, highlighting its multifaceted influence on AD pathogenesis (Ando K et al 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated implications of downregulated circFASTKD1 and circGF2I (Gao WQ et al 2020 ; Yuan C et al 2022 ) associated with myocardial infarction. Similarly, these circRNAs have also been observed in an intersection between cardiovascular and neurodegenerative disease pathways (Huang L-Y et al 2023 ). Furthermore, the linear counterpart of the PICALM’s dysregulation influences the risk of AD development by impacting APP processing, Aβ transcytosis and tau progression, highlighting its multifaceted influence on AD pathogenesis (Ando K et al 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…Midlife adiposity and late-life weight loss are frequently linked to a higher risk of cognitive decline and AD in observational studies [ 9 , 10 ]. However, the exact nature of this relationship remains a source of controversy and may even involve reverse causation between a decline in body mass index (BMI) in later life and AD [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Beyond serving as a depot for energy storage, white adipose tissue also functions as an endocrine organ, secreting a variety of biologically active substances.…”
Section: Introductionmentioning
confidence: 99%